Clostridioses em ruminantes na região sul do Rio Grande do Sul - Quevedo, Pedro de Souza (2010)
A retrospective study of clostridial diagnosed in ruminants from 1978-2008 in southern Rio Grande do Sul, was conducted in the influence area of the Regional Diagnostic Laboratory of the Federal University of Pelotas. Out of 5.446 bovine specimens sent by practitioners or from necropsies performed 91 (1,67%) were diagnosed as clostridiosis. Of those, 30 (0.55%) were diagnosed as by black leg, 15 (0.27%) as bacillary hemoglobinuria, 9 (0.16%) as botulism, 9 (0.16%) as malignant edema, and 28 (0.51%) as tetanus. Out of 860 sheep specimens 49 (5.69%) were bacterial diseases and 14 (28,57%) of those were diagnosed as clostridiosis, being 10 (1.16%) cases of tetanus, 3 (0.34%) of malignant edema, and 1 (0.11%) %) of enterotoxemia. It was concluded that some clostridiosis cause important losses in livestock in Rio Grande do Sul, mainly black leg. The vaccination of young stock against black leg is recommended in the whole state. Vaccination against botulism is recommended in areas of native pastures where phosphorus deficieny occurs, and vaccination against bacillary hemoglobinuria is recommended in low lands where fasciolosis is enzootic. In cattle, tetanus may occur as outbreaks with significant economic losses, recommending also the vaccination of animals. In sheep clostridioses are less important being tetanus the more frequent. Good hygienic practices, mainly during castration or tail are recommended to prevent the disease. Enterotoxemia is a rare disease in the region, because most sheep are raised in native pastures with limited grass production; vaccination is only recommended in sheep grazing in cultivate pastures or supplemented with concentrates.